Awakening, condensation, and sedimentation: the correlation mechanism between topics and emotions in online public opinion from the psychosocial anchoring perspective - Yu, Hong; Ma, Menglan; Yu, Xiangrong; Fang, Peng (Frontiers in Psychology, 2025)
Emotions significantly shape how publics interpret and engage with crises on social media, yet most public-opinion research treats thematic structures and affective dynamics in isolation. Drawing on social representation theory and psychosocial anchoring, this mixed-methods study examines the interplay of topics and emotions during the 2023 “Rat Head and Duck Neck” food safety incident on Chinese social media. By analyzing posts through LDA topic modeling, TextCNN-based sentiment analysis, and qualitative content analysis, the analysis reveals three dominant emotions: disgust, anger, and satire, and three central topics: food, trust, and power. These elements co-evolve via three interaction patterns: awakening, condensation, and sedimentation. These patterns not only map the evolution of online discourse but also reveal psychosocial mechanisms critical for designing more emotionally attuned digital risk-communication and management strategies in food safety crises.